Новый подвид ящурки гобийской — Eremias przewalskii tuvensis ssp. n. (Sauria, Reptilia) из Тувинской АССР и данные по систематике вида в целом - Щербак, Н.Н. (Вестник зоологии, 1970)
Анализ результатов исследования популяций Eremias przewalskii
позволил установить, что севернее Монгольского Алтая обитает особый подвид ящурки гобийской— Е. p. tuvensis. Приведены его описание и сравнение с номинальной формой. Analysis of the results of the investigations of populations Eremias przewalskii showed, that they may be divided into 2 groups E. przewalskii tuvensis ssp. n. with the area
to the north of the Mongolian Altai and E. przewalskii przewalskii (str.) with the area
to the south of this moun'ain system. Ne w subspecie s differs from the nominal by smaller
dimensions of individuals (L ma x 72(75 mm), less quantity of the spine scole (Sq M =
= 51—52), by less quantity of femoral pores (P. f. M=11.3) , by more quantity of ventral
plates (ventr. m = 36) and a'.so by the fact that a number of their femoral pores does not
reach the flexion of the limbs and back is with network pattern, and coarse-stained pattern
(as in a hrflf of alashansky individuals) doe s not occur at all.